2021
DOI: 10.3390/jcm10173836
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Sleep and Chronic Spinal Pain: A Systematic Review from the Last Decade

Abstract: Chronic spinal pain, including both neck and low back pain, is a common disabling disorder in which sleep problems are frequently reported as a comorbidity. The complex processes of both sleep and chronic pain seem to have overlapping mechanisms, which may explain their often established bidirectional relationship. This systematic review aims to investigate the assumed association between sleep and chronic spinal pain by providing an overview of the literature from the last decade. Eligible studies were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 70 publications
3
23
0
2
Order By: Relevance
“…Similarly, evidence on the effect of pain duration on pain intensity is contradictory. The data from Nicassio et al [ 14 ], Luyster et al [ 13 ] and Van Looveren et al [ 6 ] showed no effect, while O’Brien et al [ 12 ] described that duration of pain predicts a more significant pain in CLBP individuals. The difference between our results and those of Sezgin et al [ 10 ] and O’Brien et al [ 12 ] regarding the effect of pain duration on SQ and pain could be down to the heterogeneity of diagnoses and pain durations of the individuals included in our study (35.96% acute vs. 64.04% chronic).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, evidence on the effect of pain duration on pain intensity is contradictory. The data from Nicassio et al [ 14 ], Luyster et al [ 13 ] and Van Looveren et al [ 6 ] showed no effect, while O’Brien et al [ 12 ] described that duration of pain predicts a more significant pain in CLBP individuals. The difference between our results and those of Sezgin et al [ 10 ] and O’Brien et al [ 12 ] regarding the effect of pain duration on SQ and pain could be down to the heterogeneity of diagnoses and pain durations of the individuals included in our study (35.96% acute vs. 64.04% chronic).…”
Section: Discussionmentioning
confidence: 99%
“…In line with Treede et al [ 26 ], the variable Pain included the following factors: pain intensity (static, at movement and average of the last 7 days), interference of pain in daily activities and distress relative to pain. A model was analyzed in which the SQ variable predicts the pain variable based on the current evidence describing that SQ predicts pain more strongly than pain predicts SQ [ 4 , 5 , 6 ]. Additionally, the variables sex and duration of pain were included in the model to control SQ and pain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some inevitable limitations should also be mentioned. Firstly, our study cannot evaluate the influence of within-population structures resulting from the between-sex difference in the prevalence of insomnia ( Aili et al, 2015 ; Van Looveren et al, 2021 ). Secondly, MR does not inherently completely expel unknown pleiotropy that affected our results.…”
Section: Discussionmentioning
confidence: 99%
“…Although many observational studies have revealed a bidirectional relationship between sleep disturbances and LBP, the causal association are unclear due to the confounders ( Kelly et al, 2011 ; Goforth et al, 2014 ; Uhlig et al, 2018 ; Ho et al, 2019 ; Bilterys et al, 2021 ; Oliveira et al, 2022 ). A recent review focused on the association between sleep and spinal pain (including LBP) showed weak to moderate evidence of causality ( Van Looveren et al, 2021 ). Thus, further research with more advanced methodology is necessary to establish a cause-and-effect link exists between LBP and sleep disturbances.…”
Section: Introductionmentioning
confidence: 99%